Model−Driven Support for a Vaccine Study in Kathmandu - Davies, J; Gibbons, J; Harris, S; Metz, J; Pollard, A; Snape, M (2009)
We report on the use of model-driven semantic technologies in support of a study into the effectiveness of paediatric vaccination against pneumococcal disease in Nepal.